Delivering Peer-Based Support in Prisons During the COVID Pandemic and Lockdown: Innovative Activities Delivered by People Who Care - Best, David (International journal of offender therapy and comparative criminology, 2024)
During COVID and lockdown, many prisoners have not only been affected by infection transmission in crowded and ill-equipped institutions, they have also been separated from a range of supports, including loss of family and professional supports and support for prisoners with addiction and/or mental health problems has been disrupted. This paper reports on evidence of how peer-based recovery organizations have attempted to mitigate these adverse effects, based on a case study of one prison in the North-West of England, using a range of routine reporting data and original research data. The paper shows how prison-based peer recovery support has not only continued through lockdown but grown both in the prison and in continuing care on release. The key conclusion is that Lived Experience Recovery Organizations (LEROs) have a vital role to play in offering continuing care to prison populations both to support early recovery and to sustain change around release back into the community, in COVID but also more generally.